Landscape-scale variability of soil health indicators: Effects of cultivation on soil organic carbon in the Usambara Mountains of Tanzania - Winowiecki, Leigh Ann; Vågen, Tor-Gunnar; Lyamchai, Charles; Sayula, George; Msoka, Elizabeth (2015)
During the Phase I of the CCAFS project we conducted a systematic land and soil health assessment in Lushoto District in November 2012. These data were used to inform climate-smart agricultural interventions for the IFAD project as well as to parameterize DSSAT crop models for maize and beans. The land and soil health assessment that was carried out using the Land Degradation Surveillance Framework (LDSF). These data were also used to assess the effect of cultivation on soil organic carbon dynamics across the landscape. Finally, these data provide a biophysical assessment for the Lushoto CCAFS Climate Smart Village.